Considerations for Choosing Soluble Immune Markers to Determine Safety of Novel Vaginal Products - Happel, Anna-Ursula; Sivro, Aida; Liebenberg, Lenine; Passmore, Jo Ann; Mitchell, Caroline M. (Frontiers in Reproductive Health, 2022)
Several soluble cytokines have been associated with microbicide-induced cervicovaginal inflammation, non-optimal vaginal microbiota, and risk of HIV acquisition. Many of these biomarkers are used in preclinical assays to estimate the safety of vaginally applied products. However, there are currently no validated biomarkers to evaluate the safety of novel vaginal products in clinical trials. This hinders the rapid and rational selection of novel products being tested in first-in-human trials. We reviewed available literature to assess how best to select and measure soluble immune markers to determine product safety in first in human clinical trials of novel vaginal products.